A cohesive XFEM model for simulating fatigue crack growth under various load conditions. (1st May 2021) - Dekker, R.; van der Meer, F.P.; Maljaars, J.; Sluys, L.J.
Abstract: This study presents calibration and validation of a cohesive extended finite element model for fatigue crack propagation in ductile materials. The approach relies on a separation between plasticity around the crack tip and fatigue crack growth at the crack tip such that the influence of plasticity on fatigue driving forces is predicted. This implies that characterization of crack growth requires effective Paris parameters. It is shown that the calibrated model can capture fatigue crack growth behaviour in ductile materials for in-phase and out-of-phase biaxial fatigue loading as well as in-phase biaxial loading with an overload. Highlights: A cohesive XFEM model for fatigue crack growth in ductile materials is calibrated. The model can capture retardation after biaxial loading with an overload. In-phase and out-of-phase biaxial loading is investigated. Including plastic material behaviour is crucial for predicting fatigue crack growth in nontrivial load scenarios.